2008
DOI: 10.1177/1069072708329034
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of the Career Beliefs Inventory on a Sample of Italian High School Students

Abstract: This study was an examination of the validity of Krumboltz's Career Beliefs Inventory in a sample of Italian high school students (N = 256). The factor structure was examined at the item level using exploratory factor analysis. A five-factor structure emerged during analysis highlighting beliefs about Career Confidence, Career Activity, Career Independence, Career Flexibility, and Career Positivity. These factors appear to have little overlap with the results of other studies examining American and other cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…A CFA of the U.S. version using the normative data set has not been reported in the research literature by the authors, although Leierer, Strauser, and Gander (2012) confirmed the factor structure on an independent data set. We expected that the factor structures of the K-CTI generated from the three age-groups would be different from original factor solution, given the potential influence of culture on the meaning of items included in the CTI and prior research (Björnsdóttir, Kárdal, & Einarsdóttir, 2010; Hess, Tracey, Nota, Ferrari, & Soresi, 2009). If so, we would then explore the relationships among items of the K-CTI within each age-group using EFA to identify possible alternative factor structures.…”
Section: Purpose Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…A CFA of the U.S. version using the normative data set has not been reported in the research literature by the authors, although Leierer, Strauser, and Gander (2012) confirmed the factor structure on an independent data set. We expected that the factor structures of the K-CTI generated from the three age-groups would be different from original factor solution, given the potential influence of culture on the meaning of items included in the CTI and prior research (Björnsdóttir, Kárdal, & Einarsdóttir, 2010; Hess, Tracey, Nota, Ferrari, & Soresi, 2009). If so, we would then explore the relationships among items of the K-CTI within each age-group using EFA to identify possible alternative factor structures.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…Recent studies have also revealed cultural differences pertaining to relationships between and among career thoughts. Hess, Tracey, Nota, Ferrari, and Soresi (2009), when exploring the factor structure of the career beliefs inventory (CBI; Krumboltz, 1991), showed that Italian high school students may have a different structure of career beliefs than do Americans. They found that item compositions of the factors retained from a sample of Italian high school students were different from the items associated with the factors of the American samples.…”
mentioning
confidence: 99%